Masters of Greek thought Plato, Socrates, and Aristotle - Bartlett, Robert C., 1964- (Chantilly, VA : Teaching Company, 2008)
"This course will explore the thought of three profoundly influential thinkers in the Western tradition, thinkers whose very names call to mind the spirit of philosophizing or the 'love of wisdom': Socrates (469-399 B.C.), Plato (c. 429-347 B.C.), and Aristotle (384-322 B.C.). The three are most obviously linked by their historical epoch and their common devotion to the search for the truth. But they also share a more immediate bond, for Socrates was the teacher of Plato, and Plato in turn became the teacher of Aristotle. Taken together, then, Socrates, Plato, and Aristotle constitute one of the most remarkable flowerings of the human mind, and this course will explore their path-breaking attempts to grasp the world as it is in truth of 'according to nature.'" -- p. 1 [booklet 1].
Part 3 of 3 (Lectures 25-36): Aristotle and the Socratic legacy -- The problem of happiness-- Ethics 1 -- Introduction to moral virtues-- Ethics 2 -- The principal moral virtues-- Ethics 3-5 -- Prudence, continence, pleasure-- Ethics 6-7 -- Friendship-- Ethics 8-9 -- Philosophy and the good life-- Ethics 10 -- The political animal-- Politics 1-2 -- Justice and the common good-- Politics 3 -- Aristotle's political science-- Politics 4-6 -- The best regime-- Politics 7-8 -- Concluding reflections
DVD.
In three containers.
Professor Robert C. Bartlett of Emory University.
Keywords: Socrates; Plato; Aristotle